Cairo pop : youth music in contemporary Egypt - Gilman, Daniel J., 1978- (University of Minnesota Press, 2014)
Cairo Pop is the first book to examine shababiyya, the dominant popular music of Egypt that plays incessantly in Cairo, even while Egyptian youth joined in mass protests against their government. Daniel J. Gilman, who lived in Cairo at the time of the revolution, analyzes the relationship between massmediated popular music, modernity, and nationalism in the Arab world.